Search for new antibiotic and analgesic agents from higher plants and a fungus sp - Sta. Ana, Susan Tropa (Animo Repository, 1998)
Pure and semi-pure isolates were obtained from Entada phaseoloides, Amorphophallus campanulatus, and Polyporus sp. Graded extraction and a series of chromatographic separation of Entada phaseoloides afforded pure isolates EP2B2A, EP3A4A and EP1A1 identified as chondrillsterol (1), spinasterol (2) and a fatty acid or its derivative respectively.Two pure isolates, NU3C1 and NU1A, from the alcoholic extract of Polyporus sp. were also obtained. NU3C1 was identified as stellasterol (3) which has been previously isolated from other Polyporus sp. and NU1A was tentatively identified as an oxygenated sterol (4).A similar skeletal structure was likewise obtained from the alcoholic extract of Amorphophallus campanulatus however C-3 is not in the oxidized form.Analgesic test done on the crude extracts and selected fractions of Entada phaseoloides and Amorphophallus campanulatus showed that they have high potential analgesic property even higher than that of the standard mefenamic acid (EP3 = 59 percent, AC=65 percent, mefenamic acid=55 percent). Polyporus sp. on the other hand showed very high antifungal property particularly against Trichophyton mentagrophytes, the microorganism which causes many types of ring worm. Isolate NU1A was found to have less intense activity against Trichophyton mentagrophytes (A1=1.5 A1 of Clotrimazole=3.0).